2021
DOI: 10.1055/s-0041-1725134
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Concussion and Persistent Postconcussive Symptoms

Abstract: Concussion and persistent postconcussive symptoms (PPCS) are encountered by clinicians in sports medicine, pediatrics, neurology, physiatry, emergency medicine, and primary care. Clinical management may require a multidisciplinary approach. This article presents a structured method for the diagnosis of concussion and PPCS in the outpatient setting, which includes a history, physical examination, and additional tests as clinically indicated to help identify underlying symptom generators. Treatment for concussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Multidisciplinary approaches could incorporate a combination of neuroimaging in conjunction with neuropsychological measures, and self-report questionnaires, that includes both objective biomarkers and standardized scores, in addition to more subjective profiles. 115 , 120 , 121 Doing so would paint a clearer picture as to a particular presentation, in addition to consistent biological targets.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary approaches could incorporate a combination of neuroimaging in conjunction with neuropsychological measures, and self-report questionnaires, that includes both objective biomarkers and standardized scores, in addition to more subjective profiles. 115 , 120 , 121 Doing so would paint a clearer picture as to a particular presentation, in addition to consistent biological targets.…”
Section: Discussionmentioning
confidence: 99%
“…No PPCS symptoms are specific to PPCS. Assessment and treatment must therefore be comprehensive, considerate of the individual presentation and history and encompass the multiple contributing aetiologies (Quinn et al, 2018; Wilber et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that sports and other recreational activities result in between 1.6 and 3.8 million concussions annually in the U.S. ( 2 ). Moreover, 15% of mTBI patients suffer from post-concussion syndrome (PCS) characterized by delayed recovery after 3–4 weeks with physical, cognitive, and emotional complaints including headaches, poor sleep, poor concentration, dizziness, and irritability ( 3 , 4 ). Furthermore, it has been reported that concussed subjects are at three times higher risk of depression even decades after the injury ( 5 ) with characteristic imaging patterns of white matter tracts ( 6 ).…”
Section: Introductionmentioning
confidence: 99%